Investigação confirmatória de área contaminada: estudo de caso de um conjunto habitacional de interesse social - Loria, Giovana Lamano (Universidade Federal de São Carlos, 2023)
Studies related to soil and groundwater contamination are becoming increasingly relevant in the global context, due to the increase in the number of affected areas. In the state of São Paulo, industrial activities are responsible for the registration of 1294 contaminated areas, representing 20% of the total. In this context, the present work aims to study an area suspected of contamination in the municipality of Guarulhos (SP), which, in the past, housed an industrial activity of plastic manufacturing by extrusion, and is currently under residential occupation. The development of this work, after the survey of pre-existing data, was based on the confirmatory investigation, governed by different national standards and CETESB’s orientation. Among the different methodological steps, manual drilling for soil sampling and installation of groundwater monitoring wells were highlighted, followed by chemical analyses of these components. The results obtained were analyzed against CETESB orientation values, and showed concentrations higher than acceptable in groundwater samples from 6 monitoring wells, indicating the presence of contaminants in the study area. Since there are currently no active sources or evidence of activities that could cause contamination in the study area, it was concluded that the concentrations above the guideline values are due to the industrial activity that existed in the past. However, a critical analysis of the methodology used, based on existing recommendations in the scientific literature and presented by environmental agencies, indicated the need for more detailed studies, including the use of techniques and analyses not used in this study. In this way, sufficient data would be obtained to adequately perform the human health risk assessment and to propose a reclamation project for a contaminated area.
Confirmatory investigation of a contaminated land: case study of a housing complex of social interest
Keywords: Gerenciamento de áreas contaminadas; Contaminação do solo e águas subterrâneas; Investigação de área contaminada; Management of contaminated land; Soil and groundwater contamination; Investigation of contamined land; ENGENHARIAS::ENGENHARIA CIVIL::GEOTECNICA; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::ENGENHARIA DE AGUA E SOLO::CONSERVACAO DE SOLO E AGUA